The Scent of the Gods - Cheong, Fiona (Book collections on Project MUSE., 2010)
Ideal for students and scholars of Asian American and transnational literature, postcolonial history, women's studies, and many other interconnected disciplines, this special edition of The Scent of the Gods includes a contextualizing introduction, a chronology of historical events covered in the novel, and explanatory notes. --Book Jacket.